Organization of the Internal Audit System at the Oil and Gas Company - VEINBENDER, Tatiana Leonovna (Journal of Advanced Research in Law and Economics, 2017)
The research subject of the article is the internal audit as one of the ways to control efficiency of oil and gas company activity. The aim of the study is to organize the internal audit of taxes and levies of the oil and gas company. Based on the summary program of company audit it is proposed to design the financial audit of taxes and levies. The program of audit on taxes and levies is drawn up in the form of an action pack. Practical approval of the proposed program allowed revealing a need to implement tax design. The author suggests recommended practice for the consistent implementation of the tax design through eight consolidated procedures and proposes tax management scheme for the oil and gas company. The calculations have shown that the implementation of tax coordination allows achieving significant savings of financial resources of the oil and gas company. Based on results obtained the author believes that the proposed system of internal audit of taxes and levies may serve a recommended practice for financial savings of oil and gas companies of the Russian Federation.